Practice and Challenges on the Formative Assessment System in Secondary Level Mathematics - Pandey, Yam Prasad (Journal of Jayaprithvi Multiple Campus, 2025)
Evaluation is more important at the school level in measuring learning achievement and making additional plans to raise the student's level. This study's main goals were to explore the condition of the use of formative assessment and challenges faced by the teacher while formative assessment in the mathematics classroom. This study used the interpretive research method under the qualitative research approach. The informants in this study were 4 teachers who taught at the secondary level. We applied in-depth interviews and recorded the same both in audio and video necessarily. The finding of this study shows that the large number of students in a class and the overwork load for a teacher were the main factors that influenced the internal evaluation system that has not been applied systematically. To ensure the effective use of formative assessment ought to motivate teachers, training schedules should be designed to the demands of teachers, and regular monitoring and supervision by the concerned bodies should be done regularly. The findings of this study would be useful for policymakers, curriculum designers, school management, and other stakeholders in designing policies and developing training packages for teachers.